Cabezas cortadas y otros espectáculos: violencia, patetismo y truculencia en el teatro de Calderón - Ignacio Arellano (Mélanges de la Casa de Velázquez)
This article offers an analysis of the staging of violence in Calderón’s plays, with particular stress on the resort to severed heads and their various functions in different dramatic genres. Starting from general considerations about violence at the various dramatic levels (action, characters, language, stage-setting), it examines the element of pathos, especially in tragedies, and also the comic and grotesque variations in some cases. Of all the gruesome and macabre devices used (corpses, executees, murders...), it highlights the resort to severed heads, not only as verbal references in the lines, but chiefly as a scenic element manipulated in various different ways (heads made of leather and cardboard, tables with orifices, false platters, trapdoors, etc.). It concludes that Calderón used elements of gruesome cruelty, such as severed heads and other mutilations, in various different genres and contexts, in a multiplex exploration of tragic pathos and grotesque comedy, in some cases with moralising didactic intent, and in others as a means of provoking laughter and black humour.